Assessment of the stability potential of geosystems under anthropogenic influences (Case study: Ural River) - Alissa Khassenova; Tursynkul Bazarbayeva; Abdurashit Nizamiev; Laura Kurbanova; Bayan Tussupova; Rabiga Kenzhebay; Aktoty Bekzhanova; Ardak Khamitov (Caspian Journal of Environmental Sciences)
The stability of geosystems under anthropogenic influences has become a critical area of research due to increasing human activities and their impacts on natural ecosystems. This study focuses on assessing the stability potential of geosystems in the Ural River basin, a region experiencing significant anthropogenic pressures, including agricultural expansion, industrial development, and urbanization. By integrating geomorphological, hydrological, and ecological data, this research evaluates the resilience and vulnerability of the Ural River geosystem to human-induced changes. Field surveys, remote sensing, and statistical analyses were employed to quantify the extent of anthropogenic impacts. Results indicate that approximately 40% of the river basin has undergone moderate to severe degradation, with soil erosion rates increasing by 25% over the past two decades. Additionally, water quality parameters, such as nitrate concentrations, have exceeded permissible limits by 30% in areas adjacent to agricultural zones. The study identifies key drivers of instability, including deforestation, over-extraction of water resources, and improper land-use practices. Mitigation strategies, such as reforestation, sustainable water management, and land-use planning, are proposed to enhance the geosystem's stability. This research provides a comprehensive framework for understanding the interplay between anthropogenic activities and geosystem stability, offering valuable insights for policymakers and environmental managers.